Indonesia’s Muslim Organisations and the Overthrow of Sukarno - Steven Drakeley (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
This paper explores the role of Muslim organisations in the slow overthrow of President Sukarno between 30 September 1965 and 12 March 1967. It argues that their role in the process was far more important than is usually appreciated in the literature. But the primary focus here is on the surprisingly slow and hesitant evolution of the stances taken by Muslim organisations in this period on the question of Sukarno’s presidency, as well as on the one hundred and eighty degree turn that they eventually executed. From almost unqualified support for Sukarno in 1965 Indonesia’s Muslim organisations shifted, at markedly different speeds, to vehement opposition by early 1967. This article traces the shift and seeks to explain the complex of motivations and calculations that produced it and were also responsible for its varying pace. It thereby provides revealing insights into the political thinking and practices of Indonesia’s Muslim organisations in this period of political transformation and flux.DOI: 10.15408/sdi.v21i2.1039